Nonlinear coupling tracking control for underactuated construction lifting robots with load hoisting/lowering under initial input saturations. Issue 2 (17th October 2022) - Yao, Fuxing; Zhang, Tian; Yuan, Zhe; Wang, Yonghao; Chen, Lu; Yang, Honglei
Abstract: Underactuated construction lifting robots, which have been widely concerned by erudite researchers, always contain load hoisting/lowering motion. When the cable length is utilized as a variable, construction lifting robots produce violent load swing, which affects the construction safety undoubtedly and brings great challenges to the development of the controller. Moreover, most existing controllers may not take into account issues, such as initial input saturations and poor ability to suppress load swing, and they may utilize linearization or approximation. Inspired by these phenomena, a nonlinear coupling tracking controller for underactuated construction lifting robots with load hoisting/lowering under initial input saturations is proposed. With reference to expected trajectories to ensure the smooth operation of the construction lifting robot system, the initial input saturations are considered to make the trolley and cable start stably, respectively; a coupling signal, which contains actuated variables and underactuated variables, is constructed to improve the transient control performance of construction lifting robots. Combined with theoretical derivation, simulation, and experimental verification, the proposed controller achieves superior control performance, which ensures the accurate positionings of the system, and suppresses and eliminates the load swing effectively, so as to ensure the safe construction; the proposed controller admits outstanding robustness with respect to the changes of system parameters and the adverse effects of external disturbances. The proposed controller provides a novel antiswing strategy for construction lifting robots with load hoisting/lowering, which possesses excellent practical significance.